2021
DOI: 10.3390/nano11040838
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Corrosion Resistance of Stainless Steel Welded Joint Using a Nanostructured Oxide Layer

Abstract: In this study, we fabricated a nanoporous oxide layer by anodization to improve corrosion resistance of type 304 stainless steel (SS) gas tungsten arc weld (GTAW). Subsequent heat treatment was performed to eliminate any existing fluorine in the nanoporous oxide layer. Uniform structures and compositions were analyzed with field emission scanning electron microscope (FESEM) and X-ray diffractometer (XRD) measurements. The corrosion resistance of the treated SS was evaluated by applying a potentiodynamic polari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…A characteristic austenite γ-phase iron is responsible for the three predominant peaks observed at 43.5°(111), 50.79°(200), and 74.7°( 220). 31,43 In addition, a small intensity peak has been observed in a two-step surface-treated SS sample (Figure 2B) between 20 and 40 degrees, congruent with the Fe 2 O 3 (hematite) phase of Iron oxide (ICDD 01-080-5407). This study indicates that deeper oxides on the surface of stainless steel can be formed through a two-step anodic approach.…”
Section: Structure Composition and Morphology Ofmentioning
confidence: 99%
“…A characteristic austenite γ-phase iron is responsible for the three predominant peaks observed at 43.5°(111), 50.79°(200), and 74.7°( 220). 31,43 In addition, a small intensity peak has been observed in a two-step surface-treated SS sample (Figure 2B) between 20 and 40 degrees, congruent with the Fe 2 O 3 (hematite) phase of Iron oxide (ICDD 01-080-5407). This study indicates that deeper oxides on the surface of stainless steel can be formed through a two-step anodic approach.…”
Section: Structure Composition and Morphology Ofmentioning
confidence: 99%
“…They found that the anodic films were not formed in the glycerol solution when the H 2 O concentration exceeded 3 vol% due to the anodic layers presenting higher chemical dissolution rate than oxide formation rate. Since then, the influence of some parameters on the formation of anodic layers on SS has been reported [ 22 , 23 , 24 , 25 ], while only a few researchers have analyzed its electrochemical behavior against corrosion [ 14 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%